Design of PSO Based Cascaded Multilevel Inverter with Unequal DC Sources - Mohanty, Rupali; Chatterjee, Debashis; Sengupta, Gopinath (International Journal of Engineering and Technology, 2018)
This paper focusing on, the total harmonics distortion (THD) of the output voltage is minimized by the help of a cascade multilevel inverter with non-equal DC sources using particle swarm optimization (PSO) algorithm.Â  The nonlinear transcendental equation that describing the harmonic elimination problem is solved by using many methods existing in literature. In the proposed technique, unequal DC sources are taken for the multilevel inverter, which is practical when different renewable sources are used. The desired switching angles are found out by implementing PSO algorithm which results the minimum THD. Experimental details along with simulation results of 11-level inverter are shown to validate the theory.Â
Keywords: Cascade multilevel inverter; PSO; Total harmonics distortion.